An N-periodic control for coupled systems. Issue 5 (4th April 2018) - Coll, Carmen; Sánchez, Elena
ABSTRACT: This paper analyses the stabilisation of two coupled systems described by difference equations via an N -periodic feedback control. For this, it is considered a discrete-time approach with two compartmental systems, where each system has communication with the other one. An N -periodic controller is proposed to attenuate the interconnections affecting to stability of the process. It is designed so in each interval of amplitude N, the control is only added at initial time and there is no control in the rest of the time. This feedback control ensures the stability of the closed-loop system. Finally, an example is given to illustrate the theoretical results.